The Effectiveness of Differentiated Learning in Indonesian Language Subjects at Elementary Schools - Agus Riyanto; Gunarhadi Gunarhadi; Sukarno Sukarno (Journal of Innovation and Research in Primary Education, 2026)
The COVID-19 pandemic exacerbated learning losses in literacy, necessitating effective pedagogical interventions. This study investigated differentiated instruction effectiveness within Indonesia's Merdeka Curriculum framework for sixth-grade Indonesian language education. A qualitative multiple-case study was conducted from March to May 2025 at two Sekolah Penggerak elementary schools in Central Java, Indonesia, involving 26 students and two teachers. Data collection employed document analysis of teaching modules, semi-structured interviews, and systematic classroom observations. Analysis followed the Miles and Huberman interactive model with triangulation to ensure credibility. Both teachers achieved "Very Good" ratings in module development (score: 40/44) through continuous diagnostic assessment and iterative refinement. Implementation revealed two equally effective pedagogical models: humanistic-contextual and systematic-technological approaches. Student outcomes demonstrated dramatic improvement, with classical mastery rising from baseline rates of 40-44% to 100% across cognitive, affective, and psychomotor domains. Mean cognitive scores reached 85.6 and 84.5, while maintaining individual growth trajectories. Findings extend differentiated instruction theory by demonstrating its effective integration with post-pandemic curriculum reform. Results affirm that strategic differentiation accommodates diverse pedagogical expressions while simultaneously achieving educational equity and excellence. Persistent challenges in character education integration and heterogeneous socio-emotional development indicate areas requiring sustained intervention. Future research should investigate scalability across diverse school contexts using mixed-methods designs with standardized measures.